The relation of presenting symptoms with staging, grading, and postoperative 3-year mortality in patients with stage I–III non-metastatic colon cancer - Bedir, Osman; Kızıltaş, Şafak; Köstek, Osman; Özkanlı, Şeyma (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: To evaluate the association of presenting symptoms with staging, grading, and postoperative 3-year mortality in patients with colon cancer. Materials and Methods: A total of 132 patients—with a mean (standard deviation; SD) age of 63.0 (10.0) years and of whom 56.0% were males—with non-metastatic stage I–III colon cancer were included. Symptoms prior to diagnosis were evaluated with respect to tumor localization, tumor node metastasis (TNM) stage, histological grade, and postoperative 3-year mortality. Results: Constipation and abdominal pain were the two most common symptoms appearing first (29.5% and 16.7%, respectively) and remained most predominant (25.0% and 20.0%, respectively) up to diagnosis. The frequency of admission symptoms significantly differed with respect to tumor location, TNM stage and histological grade. The postoperative 3-year survival rate was 61.4%. Multivariate logistic regression revealed that melena and rectal bleeding increased the likelihood of 3-year mortality by 13.6-fold (p=0.001) and 4.08-fold (p=0.011), respectively. Conclusion: Our findings revealed differences in presenting symptom profiles with respect to the time of manifestation and predominance as well as to the TNM stage, histological grade, and tumor location. Given that melena and rectal bleeding increased the 3-year mortality risk by 13.6-fold and 4.08-fold, respectively, our findings indicate the association of admission symptoms with outcome among patients with colon cancer.